2019
DOI: 10.1108/jpmd-05-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

The role of public markets in urban habitability and competitiveness

Abstract: Purpose The purpose of this paper is to examine public market functions in three different continents (Europe, North America and Asia) and to identify a set of planning implications for their use in contexts of urban regeneration. Design/methodology/approach The paper presents a comparative analysis of four downtown market functions based on the LABiMAAM framework: [L]ocation; [A]ccessibility; [B]uilding; [i]nternal structure; [M]ain trading area; [A]menities and services; [A]nimation program; and [M]anageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…After all, food availability is a result of business location decisions. Studies have shown that in recent decades, the suburbanization of North American food retailers has contributed to the emergence of urban food deserts/swamps or disadvantaged urban areas where it is relatively difficult to obtain healthy and affordable food (e.g., [ 17 , 47 ]). Policies to improve public health and the built environment must also recognize the potential impact of suburbanization on access to healthy and affordable food.…”
Section: Discussionmentioning
confidence: 99%
“…After all, food availability is a result of business location decisions. Studies have shown that in recent decades, the suburbanization of North American food retailers has contributed to the emergence of urban food deserts/swamps or disadvantaged urban areas where it is relatively difficult to obtain healthy and affordable food (e.g., [ 17 , 47 ]). Policies to improve public health and the built environment must also recognize the potential impact of suburbanization on access to healthy and affordable food.…”
Section: Discussionmentioning
confidence: 99%
“…Both locations and types of market installations have been highlighted in several studies as being particularly interesting [ 34 , 35 , 36 ]. The present study found that the type of market installation had no influence on conditioning consumer preferences.…”
Section: Discussionmentioning
confidence: 99%
“…5.1 Managerial implications 5.1.1 Assess and position the market from diverse experiential dimensions. For towns and cities, markets have several positive social, financial, macro-spatial, environmental impacts, which make places more habitable and competitive (Balsas, 2019), and are regarded as one of the influential and controllable factors that foster town centre vitality and viability (IPM, 2019). However, many markets in the UK have suffered from decreasing footfall and the rising costs of floor space (Airey, 2017), and consequently may need to "re-invent" themselves to survive.…”
Section: Discussionmentioning
confidence: 99%